Restoring Ruhiology Quotient in 21st Century Holistic Education - Iskandar, Iskandar (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Technological advances in the Industrial Revolution 4.0 and Society 5.0 eras have facilitated access to information, but have also led to negative impacts such as identity and spiritual crises, known as